2013
DOI: 10.1371/journal.pone.0057489
|View full text |Cite
|
Sign up to set email alerts
|

The NF-κB RelB Protein Is an Oncogenic Driver of Mesenchymal Glioma

Abstract: High-grade gliomas, such as glioblastomas (GBMs), are very aggressive, invasive brain tumors with low patient survival rates. The recent identification of distinct glioma tumor subtypes offers the potential for understanding disease pathogenesis, responses to treatment and identification of molecular targets for personalized cancer therapies. However, the key alterations that drive tumorigenesis within each subtype are still poorly understood. Although aberrant NF-κB activity has been implicated in glioma, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 41 publications
2
69
1
Order By: Relevance
“…resulted in the suppression of tumorigenesis in vivo (45). Intriguingly, it is reported that RAS/PI3K/Akt/IKK/NF-B pathway activated by PDGF was associated with anti-apoptotic signaling (46).…”
Section: Discussionmentioning
confidence: 98%
“…resulted in the suppression of tumorigenesis in vivo (45). Intriguingly, it is reported that RAS/PI3K/Akt/IKK/NF-B pathway activated by PDGF was associated with anti-apoptotic signaling (46).…”
Section: Discussionmentioning
confidence: 98%
“…In agreement with our current findings indicating that RelB regulates YKL-40 expression, RelB is strongly expressed in mesenchymal subtype of GBM and promotes expression of mesenchymal genes, including YKL-40 (63). Furthermore, loss of RelB expression attenuates GBM cell survival, motility and invasion (64). …”
Section: Discussionmentioning
confidence: 99%
“…NFκB complex activates MMP-9 and several other genes which are key response elements in the tumorigenesis and stem cell maintenance through tumor microenvironment mediated inflammation and ECM signaling [30] [31,32]. To test the activation of inflammatory mediators we checked the NFκB activation in the HA-treated spheroids.…”
Section: Activation Of Nfκb Signaling In U251mg-p1 Cellsmentioning
confidence: 99%